Comparison of different methods of measuring albumin concentration in ring-necked pheasants - Schmidt, Elizabeth Moreira dos Santos [UNESP]; Paulillo, Antonio Carlos [UNESP]; Locatelli-Dittrich, Rosangela; Beltrame, Olair Carlos; de Oliveira, Edson Gonçalves (Springer Nature, 2013)
The purpose of this study was to compare albumin concentrations in ring-necked pheasants (Phasianus colchicus) using two different dye-binding methods: the bromocresol green (BCG) and bromocresol purple (BCP). High positive correlation was observed for albumin in BCG and BCP methods. Compared to BCP, the BCG-binding method yielded significantly higher (p < 0. 0001) albumin values for adult female ring-necked pheasants. © 2012 Springer-Verlag London Limited.
Keywords: Albumin; Avian; Bromocresol green; Bromocresol purple; Pheasants